Crimes of the future : theory and its global reproduction - Rabaté, Jean-Michel (Bloomsbury, 2014)
The decade since the publication of Jean-Michel Rabaté's controversial manifesto The Future of Theory saw important changes in the field. The demise of most of the visible French or German philosophers, who had produced texts that would trigger new debates, then to be processed by Theory, has led to drastic revisions and starker assessments.